Investigation of the effect of pressure on thermodynamic properties and thermoelastic phase transformation of CuAlNi alloys: A molecular dynamics study - Tatar, Cengiz; Kazanc, Sefa (Elsevier Science Bv, 2012)
Thermoelastic phase transformations and thermodynamic properties of CuAlNi alloys at 0, 1, 2 and 3 GPa pressures were investigated by using MD simulation in this study. The interactions between atoms were modelled by Sutton-Chen type of embedded atom method (SCEAM) that is based on many-body interaction. It was observed that thermoelastic phase transformation in the ternary alloy system occurred at the end of thermal process. Radial distribution function (RDF) was used in order to analysis the structures obtained from MD simulation using the simulation techniques' thermodynamic parameters. The transformation temperatures, enthalpy and entropy of the ternary alloy system have been observed to be changing with the applied pressure. In addition, it was found that the elastic energy has been decreased about 22% by applied pressure whereas Gibbs free energy has been increased about 60% by applied pressure. The values of the thermodynamical parameters obtained in this study were observed to be in close agreement with the experimental study. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Molecular dynamic; Embedded atom method; Thermoelastic phase transformation; Elastic energy; Gibbs free energy